(untitled) (Research, Society and Development, 2023)
The population of domestic animals is constantly growing, with emphasis on the population of cats, which had a greater growth than that of dogs, in Brazil, in 2021. years old. The concern for the health of felines has gained attention due to their proximity to humans. Among the various conditions that affect cats, anemia stands out, characterized as an inability to distribute oxygen to body tissues due to a reduction in the amount of circulating erythrocytes or a reduction in the concentration of cellular hemoglobin. The identification and classification of anemia cases is essential for identifying the underlying cause and stipulating the appropriate treatment. Anemia is identified based on the blood count, by analyzing the hematocrit below the reference value for the species. The classification of anemia is based on the analysis of the hematimetric indices (VCM and CHCM) and the bone marrow response (presence of anisocytosis, polychromasia and reticulocyte count), in addition, other complementary tests can be associated with the blood count to identify the cause primary cause of anemia, such as serum biochemistry. This article aims to present the main characteristics about anemia, to present the forms of classification based on hematimetric indices and bone marrow response, still, to present the main biochemical exams evaluated together with the anemia pictures, also, to bring the main particularities found in the feline species that make it different from other species.